Short term change of sea climate and influence on the littoral of Belvedere Marittimo (Cosenza - Italy) - Calise, Gianfranco; Jona Lasinio, Giovanna; Mastrantonio, Gianluca; Bruschi, Antonello; Davoli, Lina (Italian journal of engineering geology and environment, 2018)
<span data-sheets-value=""1":2,"2":"In Italy, during the last decades, the coasts have undergone an intensification of erosive processes. This has led to many problems due to the proximity of communication routes (like roads and railways) and inhabited areas to the coast. One of the most affected areas is the coast of Belvedere Marittimo, located on the Tyrrhenian side of Calabria, South Italy. The erosional crisis of the beaches is certainly due to the increasingly urbanization of the territory, both coastal and inland, which prevents normal sediment influx that feed the beaches. However, it is equally true that there are wellknown global scale changes of climate, which it is possible that are causing an increase storm intensity of tropical hurricanes and extra tropical storms. The Mediterranean Region has showed different behaviors related to local factors, with some exceptions to the general trend showing an increase of extreme events, related to wind speed and direction and therefore with effects on sea climate. In this scenario, the coast of Belvedere Marittimo will be the area of interest of the project, as previous works on the location has showed a correlation to the shoreline retreat with the increase of wind extreme events, especially in the 2001-2010 period. The decision to focus the research on wind data allows overcoming one of the most common problems of this type of studies in Italy, which is the shortage of wave data. This area has already been object of different sea defenses during the decades, but the breakwaters and groins, built for more than thirty years, did not produce significant progradation of the beaches. The proposed methodology is applicable in a microtidal regime where dominates the wave climate, and is easily exportable on the beach near an anemometric station, capable of providing historical data series thus fill the data gap on the waves. Moreover, the evaluation of changes in speed and direction of the winds / waves will allow a rethinking of the types of defenses along the beaches."" data-sheets-userformat=""2":15233,"3":"1":0,"10":1,"11":3,"12":0,"14":"1":2,"2":0,"15":"Arial","16":8">In Italy, during the last decades, the coasts have undergone an intensification of erosive processes. This has led to many problems due to the proximity of communication routes (like roads and railways) and inhabited areas to the coast. One of the most affected areas is the coast of Belvedere Marittimo, located on the Tyrrhenian side of Calabria, South Italy. The erosional crisis of the beaches is certainly due to the increasingly urbanization of the territory, both coastal and inland, which prevents normal sediment influx that feed the beaches. However, it is equally true that there are wellknown global scale changes of climate, which it is possible that are causing an increase storm intensity of tropical hurricanes and extra tropical storms. The Mediterranean Region has showed different behaviors related to local factors, with some exceptions to the general trend showing an increase of extreme events, related to wind speed and direction and therefore with effects on sea climate. In this scenario, the coast of Belvedere Marittimo will be the area of interest of the project, as previous works on the location has showed a correlation to the shoreline retreat with the increase of wind extreme events, especially in the 2001-2010 period. The decision to focus the research on wind data allows overcoming one of the most common problems of this type of studies in Italy, which is the shortage of wave data. This area has already been object of different sea defenses during the decades, but the breakwaters and groins, built for more than thirty years, did not produce significant progradation of the beaches. The proposed methodology is applicable in a microtidal regime where dominates the wave climate, and is easily exportable on the beach near an anemometric station, capable of providing historical data series thus fill the data gap on the waves. Moreover, the evaluation of changes in speed and direction of the winds / waves will allow a rethinking of the types of defenses along the beaches.